Using Geostatistics to Generate a Geological Model of a Sandstone Petroleum Reservoir in Southern California - Vasquez, Diego; Swift, Jennifer (Geographica Pannonica, 2022)
A variogram-based two-point geostatistical approach was applied to generate a geological model of a petroleum reservoir. The geology consists of a sandstone formation with uniformly inclined rock strata of equal dip angle structurally trapped by surrounding faults. Data exploration of electrical well logs using univariate/bivariate statistical tests and data transformation tools demonstrated the data to be statistically suitable for ordinary kriging and sequential Gaussian simulation. Three directions were defined as part of the variogram and the data were interpolated resulting in a 3D subsurface representation. Validation included performing a leave-one-out cross-validation for each well and statistical comparison of multiple realizations generated from a computed stochastic model. The results display a reliable geological model which indicate a direct causation of the continuity trends from the bedding attitude of the regional fault trap.
Keywords: Reservoir Characterization; Ordinary Kriging; Conditional Simulation; Geostatistics; GIS; Petroleum Geology; Los Angeles Basin